2015
DOI: 10.1097/scs.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patients Who Underwent Nasal Reconstruction After Non-Melanoma Skin Cancer Excision

Abstract: Obtaining tumor-free borders and a pleasing aesthetic result are major concerns in nasal reconstruction. Defect reconstruction and cosmesis are as important as rapid recovery and quick return to normal daily activities, and these should be considered before performing any procedure, particularly in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The RF was firstly described by Limberg and has been popularized for wound closure [13][14][15][16]. This technique proved to be effective for coverage of torso defects, such as pilonidal sinus disease and facial wounds [13][14][15][16]. However, studies focusing on the use of RF for reconstruction of limb defects are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…The RF was firstly described by Limberg and has been popularized for wound closure [13][14][15][16]. This technique proved to be effective for coverage of torso defects, such as pilonidal sinus disease and facial wounds [13][14][15][16]. However, studies focusing on the use of RF for reconstruction of limb defects are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Following this principle, if more than 50% of the subunit is apparently involved by the tumor, then surgical extirpation should extend to the whole subunit, resulting in a larger defect. Then reconstruction would be more challenging, requiring the sacrifice of a wider portion of healthy tissue [ 15 ]. Oncological clearance should be always pursued through a multidisciplinary approach, especially for large infiltrating tumors, although the extent of the residual defect after excision may result in technical difficulties for the reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using local anesthesia for reconstruction of nasal skin cancer defects reported desirable aesthetic outcomes with minimal complications and flap failures. [9][10][11] In these studies, locoregional flaps, including rhomboid flaps, glabellar flaps, bilobed flaps, nasolabial flaps, and V-Y advancement flaps, were all successfully performed with minimal complications under local anesthesia; however, more complex forehead flaps were performed under general anesthesia. [9][10][11] Due to the complexity of forehead flaps, most surgeons prefer these types of reconstructions being performed under general anesthesia; however, a few more recent studies have demonstrated that forehead flaps can be safely used for reconstruction of nasal defects under local anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In these studies, locoregional flaps, including rhomboid flaps, glabellar flaps, bilobed flaps, nasolabial flaps, and V-Y advancement flaps, were all successfully performed with minimal complications under local anesthesia; however, more complex forehead flaps were performed under general anesthesia. [9][10][11] Due to the complexity of forehead flaps, most surgeons prefer these types of reconstructions being performed under general anesthesia; however, a few more recent studies have demonstrated that forehead flaps can be safely used for reconstruction of nasal defects under local anesthesia. 12,13 In the studies 12,13 that performed forehead flaps under local anesthesia, one used tumescent local anesthesia and the other had small defects of an average side of 22 mm.…”
Section: Introductionmentioning
confidence: 99%